2018
DOI: 10.1007/s00421-018-3884-1
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of patients with a relatively greater minimum VE/VCO2 against peak VO2% and impaired exercise tolerance

Abstract: Patients with a relatively greater minVE/VCO in comparison with peak VO had impaired cardiac output as well as restricted pulmonary blood flow increase during exercise, partly due to accumulated pleural effusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“… 24 Pulmonary vasodilators have the potential risk of increasing ventilation‐perfusion mismatch and worsening the oxygenation in patients with COPD. In the present study, elevated minute ventilation/carbon dioxide production (ventilation/VCO 2 ) in the cardiopulmonary exercise test, which is a marker of ventilatory inefficiency and reflects ventilation‐perfusion mismatch, 25 and alveolar‐arterial oxygen difference, which is a marker of ventilation‐perfusion mismatch and lung diffusing capacity, also improved after BPA in patients with COPD (44.2±12.9 to 30.9±5.3; P <0.001, 47.4±33.4 mm Hg to 34.6±29.5 mm Hg; P =0.029, respectively). Various factors including dead space ratio, intrapulmonary shunt ratio, and microvasculopathy may be involved in oxygenation after BPA.…”
Section: Discussionmentioning
confidence: 77%
“… 24 Pulmonary vasodilators have the potential risk of increasing ventilation‐perfusion mismatch and worsening the oxygenation in patients with COPD. In the present study, elevated minute ventilation/carbon dioxide production (ventilation/VCO 2 ) in the cardiopulmonary exercise test, which is a marker of ventilatory inefficiency and reflects ventilation‐perfusion mismatch, 25 and alveolar‐arterial oxygen difference, which is a marker of ventilation‐perfusion mismatch and lung diffusing capacity, also improved after BPA in patients with COPD (44.2±12.9 to 30.9±5.3; P <0.001, 47.4±33.4 mm Hg to 34.6±29.5 mm Hg; P =0.029, respectively). Various factors including dead space ratio, intrapulmonary shunt ratio, and microvasculopathy may be involved in oxygenation after BPA.…”
Section: Discussionmentioning
confidence: 77%
“…Elevated VE/VCO 2 is the marker of ventilatory inefficiency and reflects ventilation perfusion mismatch [37]. Even though all possible accessible lesions had been treated after adequate BPA, our study indicated residual ventilation perfusion mismatch at not only the segmental level but also the local microvascular level, which causes exertional or nocturnal desaturation.…”
Section: Discussionmentioning
confidence: 67%
“…The European Respiratory Society Task Force on CTEPH stated that in many patients with CTEPH, resting mean PAP is normalized by surgery or multimodal treatment, and patients felt healthy; however, it is unlikely to return all pulmonary vessels back to normal [ 5 ]. VE/VCO2, which is a marker of ventilatory inefficiency and reflects the ventilation-perfusion mismatch [ 27 ], remained elevated, and %DLCO/VA, which was associated with poor outcomes in patients with CTEPH and might indicate a pronounced microvasculopathy [ 7 , 28 ], remained low in the PSP group, even though all accessible lesions had been treated after adequate BPA. However, in patients in the poorly perfused group, we considered that hemodynamics at rest improved to nearly normal, despite being poor at baseline.…”
Section: Discussionmentioning
confidence: 99%